2014
DOI: 10.3389/fnins.2014.00028
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-1 receptor blockade dysregulates REM sleep in the presence of orexin-2 receptor antagonism

Abstract: In accordance with the prominent role of orexins in the maintenance of wakefulness via activation of orexin-1 (OX1R) and orexin-2 (OX2R) receptors, various dual OX1/2R antagonists have been shown to promote sleep in animals and humans. While selective blockade of OX2R seems to be sufficient to initiate and prolong sleep, the beneficial effect of additional inhibition of OX1R remains controversial. The relative contribution of OX1R and OX2R to the sleep effects induced by a dual OX1/2R antagonist was further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 38 publications
7
72
0
Order By: Relevance
“…Recently, the U.S. Food and Drug Administration approved suvorexant (Belsomra; Merck, White House Station, NJ) for the treatment of insomnia (http://www.fda.gov/NewsEvents/Newsroom/ PressAnnouncements/ucm409950.htm). It is now well established that selective OX2R antagonists have robust hypnotic activity in preclinical species, and transient pharmacological inhibition of the two receptors, either by a dual OX1/2R antagonist or by simultaneous blockade of OX1R to OX2R antagonism, disrupts sleep architecture by shifting the balance in favor of REM sleep at the expense of NREM sleep (Dugovic et al, 2014). The role of the OX1R in emotional behavior is starting to emerge .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, the U.S. Food and Drug Administration approved suvorexant (Belsomra; Merck, White House Station, NJ) for the treatment of insomnia (http://www.fda.gov/NewsEvents/Newsroom/ PressAnnouncements/ucm409950.htm). It is now well established that selective OX2R antagonists have robust hypnotic activity in preclinical species, and transient pharmacological inhibition of the two receptors, either by a dual OX1/2R antagonist or by simultaneous blockade of OX1R to OX2R antagonism, disrupts sleep architecture by shifting the balance in favor of REM sleep at the expense of NREM sleep (Dugovic et al, 2014). The role of the OX1R in emotional behavior is starting to emerge .…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the coadministration of the OX2R antagonist JNJ-10397049 [N-(2,4-dibromophenyl)-N9-[(4S,5S)-2,2-dimethyl-4-phenyl-1,3-dioxan-5-yl]-urea] and the OX1R antagonist SB-408124 or GSK-1059865 promoted REM sleep, whereas REM sleep was not affected by either OX2R or OX1R blockade alone (Dugovic et al, 2009(Dugovic et al, , 2014. Consistent with these data, we found that compound 56 was devoid of sleep-promoting effects under basal conditions in rats and WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations